Live viral vaccines in transplanted patients (Swiss Medical Weekly, 2014)
Live attenuated viral vaccines (LAVV) have been used safely and with great success for decades to protect healthy patients against sometimes life-threatening diseases. The current recommendations usually contraindicate their use in immunocompromised hosts, despite an often increased risk for a severe presentation of disease. In this article, we review currently available LAVV, such as varicella-zoster, measles/mumps/rubella, influenza, polio, rotavirus, and yellow fever in patients with solid organ or haematopoietic stem cell transplantation. The current paediatric and adult experience with pre- and post-transplantation vaccination is discussed. To date, because of insufficient data, evidence-based recommendations to safely vaccinate transplant recipients are not available. Hopefully in the near future, specific recommendations will be implemented for certain LAVV in these patients.